Determination of Trace Cu(II) in Environmental Water Samples by Ionic Liquid Solvent Flotation and GF-ASS - Ma, Chunhong; Zhu, Hong; Wang, Liang; Jiang, Dayu; Wang, Quingwei; Yan, Yongsheng (Asian Journal of Chemistry, 2011)
Ionic liquid solvent flotation was established for detecting trace Cu(II) in environmental water by graphite furnace atomic absorption spectrometry (GF-AAS), with the mixture of ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]PF6) and ethyl acetate (1:1, v/v) as floating agent, tetracycline (TC) as trapping agent. It is a new method. The effects of pH of solution, the composition of the complexes, gas flow rate, floating time and interference ions were studied. The optimum conditions were ensured. When gas flow rate was 50 mL min-1 and floating time was 50 min, enrichment factor (a) of Cu(II) was up to 98 (500 mL initial sample/ 5 mL determination liquid). Linear range was 0.08-0.56 mg/L, detection limit was 0.3 μg/L. The proposed method was applied to determine Cu(II) in environmental water. Recovery was 91.5-103.0 %, RSD £ 3.6 %. This method is non-poisonous, low pollution, high enrichment factor. It is fit for analysis trace/ultra-trace Cu(II) of environmental water samples.